Cross-cultural adaptation, reliability, and construct validity of the Thai version of the Patient-Reported Outcomes Measurement Information System-29 in individuals with chronic low back pain. - Rawang, Polake; Janwantanakul, Prawit; Correia, Helena; Jensen, Mark P.; Kanlayanaphotporn, Rotsalai (Quality of Life Research, 2020)
Purpose: To culturally adapt the Patient-Reported Outcomes Measurement Information System-29 into Thai (T-PROMIS-29) and evaluate the reliability and validity of the culturally adapted questionnaire.Methods: The translation was performed using the Functional Assessment of Chronic Illness Therapy (FACIT) translation guidelines. Unidimensionality, internal consistency, and test-retest reliability at a 1-week interval for the translated measure were computed. Construct validity was evaluated by computing correlations between the T-PROMIS-29 scores and selected SF-36 scale scores.Results: The study sample comprised of 241 participants with chronic low back pain. Internal consistencies were good to excellent, with Cronbach's alphas ranging from 0.84 to 0.94. The test-retest stability of all T-PROMIS-29 domains were moderate to good, with ICCs(2,1) ranging from 0.57 to 0.74. Unidimensionality, convergent validity, and divergent construct validity were satisfactory.Conclusions: The findings support the reliability and validity of the T-PROMIS-29 scale scores. The measure can be used to assess key quality of life domains in individuals from Thailand with chronic low back pain.